My Blood's Country: a journey through the landscapes that inspired Judith Wright's poetry by Fiona Capp (Journal of the Association for the Study of Australian Literature, 2010)
My Blood's Country: a journey through the landscapes that inspired Judith Wright's poetry by Fiona Capp